Analysis of Clinical Efficacy of Traditional Chinese Medicine in Recovery Stage of Stroke: A Systematic Review and Meta-Analysis. (22nd September 2020) - Zhang, Xue; Zhang, Xiao-Fei; Wang, Lin; Guo, Dong-Yan; Zhang, Jia-Min; Chen, Yong-Gang; Wang, Zhi-Chao; Pei, Li-Shan; Chen, Jiang-Xue; Shi, Ya-Jun; Zou, Jun-Bo
Abstract : Background . We provide an updated meta-analysis with detailed information on a combination of TCM and routine treatment. Methods . Retrieve appropriate articles with no language restrictions on keywords until 8 July 2019 in an electronic database. All trajectories are screened according to certain criteria. The quality of certified research was also evaluated. We made a detailed record of the results of the measurement. Meta-analysis was carried out by using the Revman 5.3 software. Results . Sixty-seven RCTs were included, and 6594 subjects were analyzed. Compared with routine treatment, the total effective rate (TER) of TCM combined with routine treatment was improved, and the recovery of stroke was also significantly accelerated. Regulation of blood lipids by notably shrinking the contents of TC, TG, and LDL and enhancing the levels of HDL. The levels of serum hs-CRP, WHV, and WLV decreased significantly, indicating that the expression of thrombomodulin was decreased after the comprehensive treatment of traditional Chinese medicines (TCMs). The combination of TCM treatment could enhance the protection of neural function by decreasing the NIHSS scoring while increasing the BI scoring. Paeoniae Radix Rubra, Angeticae Sinensis Radix, etc., can effectively improve the clinical symptoms of stroke convalescent patients and promote the recovery of neurological function. ACU of Baihui, Renzhong, etc., can improve the clinical rehabilitation effect of patients. However, our findings must be handled with care because of the small sample size and low quality of clinic trials cited. Other rigorous and large-scale RCTs are in need to confirm these results. Conclusion . A combination of TCM and routine treatment in the treatment of stroke could improve TER, and it is beneficial to the rehabilitation of patients in the recovery period of apoplexy. These effects can be mediated by a combination of several mechanisms. Nevertheless, due to the limitations of this study, these results should be handled with caution.